Sanctions for Fish Theft According to Regulation No. 09 of 2021 in the Perspective of Islamic Criminal Law in Nagari Padang Air Dingin - Parut, Wensislaus; Sari, Respita; Zaenab Djahamao, Nurangdini (Yayasan Lembaga Studi Makwa, 2024)
This research examines the sanctions for fish theft as regulated by Regulation No. 09 of 2021 in Nagari Padang Air Dingin, from the perspective of Islamic Criminal Law. Fish theft is a significant issue in the community, and local regulations are enforced to address this crime. Regulation No. 09 of 2021 stipulates penalties for those caught stealing fish within the jurisdiction of Nagari Padang Air Dingin, aiming to protect the livelihoods of local fish farmers and ensure the sustainability of fisheries. Islamic Criminal Law offers a framework for dealing with theft, including hudud (fixed punishments), ta'zir (discretionary punishments), and reconciliation between the offender and the victim. This study analyzes how the local regulations align with or differ from Islamic legal principles concerning theft, focusing on the nature of the crime, the process of adjudication, and the punishment applied. The findings suggest that while the regulation primarily focuses on material restitution and deterrence, there is room for incorporating Islamic values such as repentance, forgiveness, and community-based resolutions in resolving cases of fish theft. By comparing local norms with Islamic criminal jurisprudence, this research highlights the potential for a more holistic approach to justice that balances punishment with moral and social rehabilitation.